2011
DOI: 10.3389/fgene.2011.00066
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Hepatobiliary and Pancreatic Cancers

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that function as endogenous silencers of numerous target genes. Hundreds of miRNAs have been identified in the human genome. miRNAs are expressed in a tissue-specific manner and play important roles in cell proliferation, apoptosis, and differentiation. Aberrant expression of miRNAs may also contribute to the development and progression of human hepatobiliary and pancreatic cancers. Recent studies have shown that some miRNAs play roles as tumor suppressors or oncoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 44 publications
(49 reference statements)
0
36
0
Order By: Relevance
“…Therefore, the antitumor effect of gemcitabine might be associated with miR-1260b inhibition. miR-222 was also recognized as oncogenic miRNA (39)(40)(41)(42)(43). The cell cycle-dependent kinase inhibitor, p27Kip1 is the target gene of miR-222 (39,40,43).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the antitumor effect of gemcitabine might be associated with miR-1260b inhibition. miR-222 was also recognized as oncogenic miRNA (39)(40)(41)(42)(43). The cell cycle-dependent kinase inhibitor, p27Kip1 is the target gene of miR-222 (39,40,43).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of miR-122 has previously been assessed through antisense oligonucleotide-mediated knockdown, implicating miR-122 in cholesterol and fat metabolism (4,5). Although HCC was not observed in the time frame of these studies, several groups have reported tumor suppressor activity for miR-122, based on decreased miR-122 levels in tumor tissue and inhibitory effects of miR-122 in tumorigenicity assays (6). However, knockdown experiments are limited by their transient nature and the potential for off-target effects.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Chemotherapeutic agents that inhibit neutrophil biogenesis (6)(7)(8) and/or reduce their bactericidal activity (7) produce neutropenia (i.e., <500,000 neutrophils/ml blood). Although neutropenia predisposes to infection, it has little direct effect on the sterility of blood because under most (9) -but not all (10) -conditions, hepatic and splenic macrophages are the cells primarily responsible for clearing bacteria from the circulation.…”
Section: Other Functions Of Mir-122mentioning
confidence: 99%
“…This suggested that Bcl-w is a direct target of miR-122 that functions as an endogenous apoptosis enhancer in HCC cells (16). Other miR-122 target genes include SRF, Igf1R, ADAM10, ADAM17 in HCC (20). In the present study, a new miR-122/DLX4 axis was …”
Section: Discussionmentioning
confidence: 49%